Why the left loses : the decline of the centre-left in comparative perspective - Manwaring, Rob; Kennedy, Paul, 1963- (Policy Press, 2018)
"Social democracy is on the back-foot, and increasingly centre-left political parties are struggling to win office. Bringing together a range of leading academics and experts on social democratic politics and policy, Why the left loses offers an international, comparative view of the changing political landscape, examining the degree to which the centre-left project is exhausted and is able to renew its message in a neoliberal age. Using case studies from the UK, Germany, Spain, France, Australia and New Zealand, contributors argue that despite different local and specific contexts, the mainstream centre-left is beset by a range of common challenges. Analysis focuses on institutional and structural factors, the role of key individuals, especially party leaders, and the atrophy of progressive ideas in explaining why the centre-left is currently in retreat. Why the left loses is aimed at stimulating wider debate about the fortunes of the centre-left"--